Alkaloids from Popowia perakensis King and their potential as Dipeptidyl peptidase IV (DPP IV) inhibitors - Syed Abdul Azziz, Saripah Salbiah; Mukhtar, Mat Ropi; A. Hadi, A. Hamid; Mhd Bakri, Yuhanis; Aldulaimi, Ahmed Kareem Obaid; Awang, Khalijah; Hashim, Yumi Zuhanis Has-Yun (A and V Publication, 2019)
A study on the alkaloidal composition on the Malaysian Annonaceae species, i.e Popowia perakensis King has been carried out. Barks of Popowia perakensis were extracted with hexane, dichloromethane and methanol, respectively. Dichloromethane extract further underwent the acid base treatment to give the alkaloidal crude extract. Isolation of compounds was carried out using various chromatography techniques including column chromatography and thin layer chromatography. Spectroscopic methods notably 1H, 13C NMR, IR, UV and GC-MS spectroscopy were utilized to identify pure compounds in addition to comparison of reported data. Two azaanthraquinones alkaloids namely cleistopholine 1 and 6-methoxycleistopholine 2 together with simple isoquinolone alkaloid, N-methylcorydaldine 3 had been isolated. All three alkaloids are known but they were isolated for the first time from this species. Cleistopholine 1 was tested for Dipeptidyl peptidase IV (DPP IV) inhibition to investigate its potential antidiabetic activities. Results revealed that this compound showed quite weak (6.26 %) inhibitory activities as compared to the positive control, Diprotin A (81.46 %). The quantity of the other two compounds was insufficient for the screening purposes.